The Increase in Efficiency of the Modes Power Resources Consumptions of the Processing Equipment of the Enterprises of Oil-processing Industry - Shokarov, Dmytro; Lazurenko, Oleksandr; Cherkashyna, Halyna; Chorna, Viktoria (My University, 2018)
The technique of static planning of an experiment for creation of mathematical model of energy consumption of technological plants of the enterprise of oil industry is offered that has allowed to analyze effectively the factors which influence the production and to optimize the expenses, to reduce the prime cost and to increase the overall performance of the enterprise in general.
Keywords: planning of an experiment; energy consumption optimization; oil-processing industry; energy resources